2004
DOI: 10.1002/pmic.200300761
|View full text |Cite
|
Sign up to set email alerts
|

UDP‐Glucose pyrophosphorylase is upregulated in carriers of the porcine RN mutation in the AMP‐activated protein kinase

Abstract: The AMP-activated protein kinase (AMPK) plays a key role in the regulation of energy metabolism in eukaryotic cells acting as a metabolic sensor. In its activated form AMPK inhibits ATP consuming pathways and stimulates ATP generating pathways. A dominant mutation, denoted RN(-), in the porcine PRKAG3 gene, encoding the regulatory gamma3 subunit of AMPK, results in hyperaccumulation of glycogen in glycolytic skeletal muscle cells. To study the effects of this mutation on protein expression patterns in skeletal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 41 publications
3
30
0
Order By: Relevance
“…Interestingly, the microarray data and qRT-PCR analysis revealed a significant up-and down-regulation of Ugp2 and Gbe1 mRNAs (encoding two key enzymes in glyocogen synthesis) in skeletal muscle from AMPK ␥3 R225Q transgenic and knockout mice, respectively. In agreement with these results, the protein level and enzyme activity of Ugp2 and Gbe1 is increased in RN pigs carrying an R225Q mutant form of the AMPK ␥3-subunit (14,47). Based on these observations, we hypothesize that the differences in the skeletal muscle glycogen re-synthesis rate displayed by ␥3 R225Q transgenic and knock-out mice may be at least partly explained by coordinated differential transcription of Ugp2 and Gbe1.…”
Section: Discussionsupporting
confidence: 73%
“…Interestingly, the microarray data and qRT-PCR analysis revealed a significant up-and down-regulation of Ugp2 and Gbe1 mRNAs (encoding two key enzymes in glyocogen synthesis) in skeletal muscle from AMPK ␥3 R225Q transgenic and knockout mice, respectively. In agreement with these results, the protein level and enzyme activity of Ugp2 and Gbe1 is increased in RN pigs carrying an R225Q mutant form of the AMPK ␥3-subunit (14,47). Based on these observations, we hypothesize that the differences in the skeletal muscle glycogen re-synthesis rate displayed by ␥3 R225Q transgenic and knock-out mice may be at least partly explained by coordinated differential transcription of Ugp2 and Gbe1.…”
Section: Discussionsupporting
confidence: 73%
“…We also showed that increased UDPG-PPL expression was independent of increased glucose uptake, because increasing glucose uptake by overexpressing glucose transporter 1 downregulated UDPG-PPL expression. Consistent with this finding, increased Ugp2 mRNA levels have also been shown in the skeletal muscle of mice (R225Q) and pigs (R200Q) bearing mutations at corresponding sites of γ3-AMPK and presenting a glycogen storage phenotype (32,33). These findings collectively suggest that upregulation of UDPG-PPL is a primary response to AMPK mutation rather than an adaptive response to altered glucose metabolism.…”
Section: Figuresupporting
confidence: 75%
“…Alternatively, the hyperaccumulation of glycogen in RN -carriers could originate from the higher expression of UDP-glucose pyrophosphorylase protein and high activity of the enzyme reported by Hedegaard et al (2004). Furthermore, Hedegaard et al (2004) suggested that the synthesis of glycogen in the muscles of RN -carriers was increased due to increased influx of glucose into the muscle fibres.…”
Section: )mentioning
confidence: 99%
“…Thus, the differences in the activity of GDE between the genotypes do not explain the faster pH decrease early post-mortem in RN -carriers compared with wild type animals. Hedegaard et al (2004) found indications of an up-regulation of phosphofructokinase enzyme in RN -carriers, which is the rate-limiting enzyme in glycolysis, and this would explain the fast glycolysis during early post-mortem in RN -carriers.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation